La tombe de Benito Mussolini à Predappio: Le culte d'un anti-héros - Giampaoli, Michelangelo [UNESP] (CAIRN, 2016)
Seventy years on since the end of World War II and the death of Mussolini, the latter's tomb in Predappio, Emilia Romagna, is a meeting place for the nostalgics of the Fascist period who gather there every year in collective commemoration on particularly symbolic occasions. Thousands of people from every part of Italy go to Predappio to pay homage to the founder of fascism, often manifesting devotional forms and practices that arouse criticism from public opinion. The local government makes little effort to confront these pilgrims - tourists, whose presence creates embarrassment but who, nonetheless, are an important contribution to the local economy. This article deals with all these contradictions.
Benito Mussolini's grave in Predappio. Paying homage to an anti-hero
Keywords: Cemetery; Fascism; Funeral tourism; Pilgrimage; Worship